Numerical and Experimental Analyses of the Effect of Heat Treatments on the Phase Stability of Inconel 792 - Maria M. Cueto-Rodriguez; Erika O. Avila-Davila; Victor M. Lopez-Hirata; Maribel L. Saucedo-Muñoz; Luis M. Palacios-Pineda; Luis G. Trapaga-Martinez; Juan M. Alvarado-Orozco (Advances in Materials Science and Engineering)
A study about the precipitation and phase stability was carried out in an IN-792 superalloy used as a blade in a gas turbine. Microstructure analysis was conducted experimentally on three different cross sections of the blade designated as high temperature (HT), medium temperature (MT), and low temperature (LT). To identify the HT, MT, and LT sections, a numerical thermal analysis was performed using ANSYS software. To obtain the distribution gradient of temperature in the blade, the real conditions of operation in steady state of the gas turbine were considered. A numerical study about the occurrence of phases in the IN-792 superalloy was carried out with Thermo-Calc and TC-PRISMA software. The analysis of the as-cast IN-792 superalloy with Scheil-Gulliver equations permitted to explain the phase formation during the solidification process. The calculated time-temperature-precipitation (TTP) diagram explains consistently the precipitation process observed after two different heat treatment conditions applied experimentally and numerically to regenerate the original microstructure of the IN-792 superalloy. The experimental results were consistent with the calculated isoplethic and TTP diagrams. In terms of accuracy, the further development of the Thermo-Calc databases for thermodynamic calculations in superalloys is evident. It was possible to calculate precipitation temperatures and the local evolution of precipitated particles for two different heat treatment conditions.